2009
DOI: 10.1038/ijo.2009.172
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal liver function test results are related to metabolic syndrome and BMI in Taiwanese adults without chronic hepatitis B or C

Abstract: Background: Metabolic syndrome (MS) is considered a cause of abnormal deposition of fat into hepatocytes, which might be associated with hepatic steatosis or abnormal liver function. Objective: The aim of this study was to explore the factors associated with MS and the relationship between MS and abnormal aspartate aminotransferase (AST), alanine aminotransferase (ALT) and g-glutamyl transferase (GGT) levels in Taiwanese subjects without chronic hepatitis B (CHB) or C (CHC). Subjects: We enrolled 2539 Taiwanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
7
21
1
Order By: Relevance
“…In our study, BMI was found to be related to abnormal AST and ALT levels, a result that was also obtained in our previous small-scale study [7]. In addition, waist circumference, one component of MS, is an indicator of obesity, and we therefore believe that a larger waist circumference might be related to abnormal liver function via a mechanism similar to that of a higher BMI value, which might be related to insulin resistance and NASH, and may explain why waist circumference was found to be related to abnormal AST and ALT levels in our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, BMI was found to be related to abnormal AST and ALT levels, a result that was also obtained in our previous small-scale study [7]. In addition, waist circumference, one component of MS, is an indicator of obesity, and we therefore believe that a larger waist circumference might be related to abnormal liver function via a mechanism similar to that of a higher BMI value, which might be related to insulin resistance and NASH, and may explain why waist circumference was found to be related to abnormal AST and ALT levels in our study.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, insulin resistance is a particular danger and can lead to mitochondrial damage, intracellular beta-oxidation, and fat depositionwithin hepatocytes [23], inducing the destruction of hepatocytes and abnormal increases in hepatic enzyme levels. In our study, abnormal AST and ALT levels were found to be related to uric acid, triglyceride, and fasting sugar levels and male gender, and in our previous small-scale study, MS was identified as being related to abnormal AST and ALT levels [7]. We therefore consider it reasonable to propose that components of MS, such as waist circumference, triglyceride level, and fasting sugar level, are related to abnormal AST and ALT levels.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Such pattern of AST and ALT has been identified in surveys of overweight and obese Chinese males [14], in spite of the fact that some defend its association with white ethnic groups only [15]. In the present cohort the difference was notorious (P=0.000).…”
Section: Discussioncontrasting
confidence: 45%